MET-9 LEPTOMENINGEAL CARCINOMATOSIS ~ ITS' ASSOCIATION WITH MOLECULAR AND PATHOLOGICAL SUBTYPES~. (3rd December 2022) - Iuchi, Toshihiko; Hosono, Junji; Setoguchi, Taiki; Hasegawa, Yuzo; Sakaida, Tsukasa
Abstract: Background: Leptomeningeal carcinomatosis (LMC) is the most difficult condition to treat brain metastases (BM), and the presence or absence of malignant cells in the cerebrospinal fluid (CSF) is important in determining treatment strategies. Here, we defined Type I LMC (CSF cytology positive) as LMC, and compared the risk of LMC in lung cancer (LC) by subtypes. Patients and Methods: In principle, at our hospital, we confirm CSF cytology when any of the following is observed: enhanced lesion in contact with the cerebrospinal fluid cavity, cranial nerve symptoms, or concurrent hydrocephalus. Of the 833 cases of BM from LC diagnosed since 2005, 794 cases, excluding 39 cases for which molecular diagnosis was not performed, were enrolled. Results: There existed EGFRm: 321 cases, ALK: 19 cases, without driver mutation (w/oDM): 313 cases, small cell lung cancer (SCLC): 141 cases. 1326 CSF cytological examinations were performed in 533 patients, and 162 were diagnosed as LMC. The frequency of LMC at diagnosis of BM was EGFRm: 8.7%, ALK: 5.3%, w/oDM: 3.2%, and SCLC: 0.0% (P<0.0001). The time to LMC from diagnosis of LC was significantly shorter in EGFRm than ALK (H.R.:4.89, P=0.027), w/oDM (H.R.:2.96, P<0.0001), and SCLC (H.R.:7.23, P<0.0001). The use of TKIs after diagnosis of LC in EGFRm patients did not prevent LMC (HR: 0.932, P=0.493). The time to LMC from diagnosis of BM was also shorter in EGFRm in compared with ALK (H.R.: 4.89, P=0.027), w/oDM (H.R.: 3.94, P=0.057), and SCLC (H.R.: 8.94, P<0.0001). L858R had a higher risk of LMC than Ex19deletion (HR: 1.59, P=0.037). Neither TKI use (HR: 0.989, P=0.971) nor radiotherapy (HR: 0.846, P=0.567) prevented LMC. Conclusion: EGFRm has a higher risk of developing LMC than other subtypes, and it is thought to be a factor in the high risk of central nervous system death in this subtype.